Wybrane aspekty zrównoważonego rozwoju obszarów przygranicznych na przykładzie działalności Euroregionu Glacensis - Cymerman, Anna (Chosen aspects of sustainable development in borderlands on the example of the activity in the Glacensis Euroregion, 2007)
The Glacensis Euroregion is an entity which, by working towards its goals, contributes to the implementation of the sustainable development strategy in the Polish-Czech borderland. Most projects carried out in this region concem the issue of sustainable development. The analysis of projects pursued in the Glacensis Euroregion between 1998 and 2005 indicates an increasing interest in using community support. The projects, the priority goals, and ventures financed within the framework of the community initiative programme Interreg IIIA confirm the thesis that it is social activity that constitutes the most important area o f interest in the Euroregion, whereas environmental issues and naturę become the subjects of projects considerably less often. The increasingly morę effective use of both EU financial support and the budget for running programmes aimed at fulfilling strategie goals of the region contribute to levelling disproportions in development. The spectacular results encourage the local community to increasingly morę active participation in projects, which in tum leads to the formation of the attitude of social responsibility for the region and provides a foundation for information society. This easily noticeable trend shows that in the futurę ventures undertaken in the Euroregion will foster sustainable development in a broader sense and take into account all its dimensions, thereby reducing disparities between social, environmental, and economic spheres.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 273-282